Properties of Phenol-Formaldehyde Resin Modified with Kraft Lignin for Particleboard Production - Miroslav Němec; Luboš Prokůpek; Jaromír Hradecký; Vojtěch Obst; Tomáš Pipíška; Štepan Hysek (Drvna Industrija)
Lignin is a natural polymer with a phenolic structure, which makes it suitable as a substitute in phenol-formaldehyde (PF) resins. In this study, unmodified kraft lignin was used as a substitute in a commercial phenol-formaldehyde resin, with the substitution rate being 10 %. This resin was further used to produce a singlelayer particleboard using hot pressing in a laboratory press. Results of physical and mechanical tests showed that the addition of lignin to the PF resin negatively affected these properties, while particleboards bonded with lignin-modified PF resin met the requirements of the standard for lower-class particleboards. Scanning electron microscopy confirmed cohesive failures in ruptured particleboards bonded with both the reference resin and the lignin-modified PF resin. For the lignin-modified PF resin, particles of undissolved lignin were found in the resin. Further testing showed no difference in the emission of volatile organic compounds between the variants.